Anti‐TIM‐1 Monoclonal Antibody (RMT1‐10) Attenuates Atherosclerosis By Expanding IgM‐producing B1a Cells. Issue 13 (3rd July 2018) - Hosseini, Hamid; Yi, Li; Kanellakis, Peter; Cao, Anh; Tay, Christopher; Peter, Karlheinz; Bobik, Alex; Toh, Ban‐Hock; Kyaw, Tin
Abstract : Background: Peritoneal B1a cells attenuate atherosclerosis by secreting natural polyclonal immunoglobulin M (IgM). Regulatory B cells expressing T‐cell immunoglobulin mucin domain‐1 (TIM‐1) expanded through TIM‐1 ligation by anti‐TIM‐1 monoclonal antibody (RMT1‐10) induces immune tolerance. Methods and Results: We examined the capacity of RMT1‐10 to expand peritoneal B1a cells to prevent atherosclerosis development and retard progression of established atherosclerosis. RMT1‐10 treatment selectively doubled peritoneal B1a cells, tripled TIM‐1 + B1a cells and increased TIM‐1 + IgM + interleukin (IL)‐10 + by 3‐fold and TIM‐1 + IgM + IL‐10 − B1a cells by 2.5‐fold. Similar expansion of B1a B cells was observed in spleens. These effects reduced atherosclerotic lesion size, increased plasma IgM and lesion IgM deposits, and decreased oxidatively modified low‐density lipoproteins in lesions. Lesion CD4 + and CD8 + T cells, macrophages and monocyte chemoattractant protein‐1, vascular cell adhesion molecule‐1, expression of proinflammatory cytokines monocyte chemoattractant protein‐1, vascular cell adhesion molecule‐1, IL1β, apoptotic cell numbers and necrotic cores were also reduced. RMT1‐10 treatment failed to expand peritoneal B1a cells and reduce atherosclerosis after splenectomy that reduces B1a cells, indicating that these effects are B1a cell‐dependent. Apolipoprotein E‐KO mice fed a high‐fat diet for 6 weeks before treatment with RMT1‐10 also increased TIM‐1 + IgM + IL‐10 + and TIM‐1 + IgM + IL‐10 − B1a cells and IgM levels and attenuated progression of established atherosclerosis. Conclusions: RMT1‐10 treatment attenuates atherosclerosis development and progression by selectively expanding IgM producing atheroprotective B1a cells. Antibody‐based in vivo expansion of B1a cells could be an attractive approach for treating atherosclerosis.